Assessing the Validity of Transformational Leadership, Motivation, and Job Satisfaction Instruments: A CVI and CCA Approach in Merangin District - Andriadi, Dian; Sulistyo, Urip; Sofyan, Sofyan; Habibi, Akhmad (FKIP Universitas Jambi, 2026)
This study aims to assess the validity and reliability of instruments measuring transformational leadership, motivation, job satisfaction, and teacher performance in senior high schools in Merangin District. A quantitative approach was employed using a two-stage validation process, namely Content Validity Index (CVI) and Confirmatory Composite Analysis (CCA). The study involved three expert validators and 75 teacher respondents. The CVI results indicated that most items achieved a high level of agreement among experts (I-CVI = 1.00), although several items (I-CVI = 0.67) required revision to improve clarity and relevance. Furthermore, the CCA results showed that all constructs met reliability criteria, with Composite Reliability (CR) values exceeding 0.70. Most indicators demonstrated adequate factor loadings (>0.70), indicating acceptable construct validity; however, several indicators fell below the recommended threshold, including one item with a very low loading that should be eliminated. Overall, the findings suggest that the instrument is generally valid and reliable, although refinement of several items is necessary to enhance measurement accuracy. This study contributes to the development of more robust and contextually appropriate measurement instruments in educational research.